2020
DOI: 10.30910/turkjans.680088
|View full text |Cite
|
Sign up to set email alerts
|

Gaziantep İlindeki Tüketicilerin Yumurta Tüketim Alışkanlıklarının Belirlenmesi

Abstract: Özet Bu çalışmanın amacı Gaziantep ili kent merkezindeki tüketicilerin yumurta tüketim davranışlarını ve tüketim tercihinde etkili olan faktörleri belirlemektir. Araştırmanın ana materyalini Gaziantep ili kent merkezinde 271 tüketici ile yapılan anketlerden elde edilen veriler oluşturmaktadır. Verilerin analizinde tanımlayıcı istatistikler, F-testi ve ki-kare testlerinden yararlanılmıştır. Araştırma bulgularına göre, tüketicilerin %96.31'inin yumurta tükettiği, hanede haftada ortalama 16.79 adet yumurta tüketi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
2
1
0
1
Order By: Relevance
“…It has been determined that the after the market most preferred egg supply way was the farmers market (19.6%) and the producer (18%), respectively. In this study, the finding that 98.5% of the consumers consumed egg in their households was found similar to the reported values by Cevger et al (2008), Mızrak et al (2012), İskender and Kanbay (2014), Alkan and Derebaşı (2018), and Aytop and Işık (2020). In the research, it was thought that the main reason for the preference of the market as a place of supply for eggs (58.3%) was the fact that the markets were more dominant and more accessible as a place of food supply.…”
Section: Demographic Characteristics Of Participantssupporting
confidence: 92%
See 1 more Smart Citation
“…It has been determined that the after the market most preferred egg supply way was the farmers market (19.6%) and the producer (18%), respectively. In this study, the finding that 98.5% of the consumers consumed egg in their households was found similar to the reported values by Cevger et al (2008), Mızrak et al (2012), İskender and Kanbay (2014), Alkan and Derebaşı (2018), and Aytop and Işık (2020). In the research, it was thought that the main reason for the preference of the market as a place of supply for eggs (58.3%) was the fact that the markets were more dominant and more accessible as a place of food supply.…”
Section: Demographic Characteristics Of Participantssupporting
confidence: 92%
“…In the research, it was thought that the main reason for the preference of the market as a place of supply for eggs (58.3%) was the fact that the markets were more dominant and more accessible as a place of food supply. The finding that the egg supply place was a market in this research was parallel to the reported values by Erdoğan (2013), Mızrak et al (2012), İskender and Kanbay (2014), and Aytop and Işık (2020). In contrast, Altan et al (1993), and Alkan and Derebaşı (2018) reported different finding from our results in terms of egg purchasing place.…”
Section: Demographic Characteristics Of Participantssupporting
confidence: 89%
“…Although the average annual fish consumption per capita in Türkiye is low in Eastern Anatolia, Southeastern Anatolia and Central Anatolia regions, it is quite high in the Black Sea and other coastal regions (Aydın & Karadurmuş, 2013;Ercan & Şahin, 2016). Similarly, per capita consumption in regions near the sea, for example, is 28.08 kg per year in Giresun and Trabzon (Aydın & Karadurmuş, 2013), 25.8 kg per year in Mersin; 21.5 kg per year (Demirtaş et al, 2014;Şen & Şahin, 2017), 15 kg per year in İzmir, 13 kg per year in Tokat, 12.4 kg per year in Isparta, 6.5 kg per year in Erzurum, 4.13 kg per year in Kahramanmaraş, 3.8 kg per year in Niğde (Hatırlı et al, 2004;Erdal & Esengün, 2008;Çaylak, 2013;Ercan & Şahin, 2016;Bashimov, 2017;Uzundumlu, 2017), and 3.4 kg per year in Ankara (Gül Yavuz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tüketim miktarının artması veya dünya ortalamasına yaklaşması için tüketim alışkanlıklarının ve üretim miktarının artırılması, tüketici alım gücünün yükseltilmesi gibi faktörlerin göz önünde bulundurulması önemlidir. Son yıllarda Türkiye'de et tüketimiyle ilgili tüketici davranışlarını belirlemeye yönelik genellikle tüketici tercihlerini, satın alma alışkanlıklarını, et tüketimi miktarlarını, tercih edilen et türlerini ve tüketim nedenlerini incelemek amacıyla birçok çalışma yapılmıştır (Tolon, 2003;Sarıözkan ve ark., 2007;Cevger ve ark., 2008;Orhan & Yüksel, 2010;Akbay ve ark., 2013;Akçay & Vatansever, 2013;Aydın & Karadurmuş, 2013;Saygı ve ark., 2015;Arslan & İzci, 2016;Balcı ve ark., 2016;Balık ve ark., 2013;Bayraktar, 2015;Bashimov, 2017;Şen, 2017;Terin ve ark., 2016;Uzundumlu & Dinçel, 2015;Karakaya & Kırıcı, 2016;Karakaya ve ark., 2018;Kırıcı ve ark., 2018;Bayraktar ve ark., 2019;Karakaya ve ark., 2020;Kuşat & Şahan, 2021). Bu çalışmalar, sektörün stratejilerini belirlemede rehberlik etmekte, yeni pazar alanlarının tespitine yardımcı olmakta ve belirli bir yer veya bölgede yaşayan insanların refahtan elde ettikleri payı ve harcamalarını ortaya koymaktadır.…”
Section: Introductionunclassified